Edukasi gizi pada ibu oleh kader terlatih meningkatkan asupan energi dan protein pada balita - Abdillah, Faza Muhammad; Sulistiyawati, Sulistiyawati; Paramashanti, Bunga Astria (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Child nutrition can have a long-term impact on the development of future human capital, particularly in relation to cognitive capability, productivity, and economic development. We aimed to investigate the influence of maternal nutrition education on energy and protein intakes of children in community feeding centers. This study used a quasi-experimental design with pre- and post-intervention control group. A total of 38 child-mother pairs were involved in this research. Mothers in the intervention group received nutritional education delivered by trained cadres for eight sessions in a period of four weeks. Nutritional intake data collection using 24-hour recall. Data were analyzed used the Dependent T-test and Wilcoxon test.Â The results showed that nutrition education by trained cadres had a statistically significant effect on increasing energy intake (p= 0,000) and also on protein intake (p= 0,001) in children under-five. Educating mothers about child nutrition significantly increased child energy and protein intake. Involving trained cadres as the educators may result in an effective intervention to improve child dietary intake.